Toward self-organized mobile ad hoc networks the terminodes project. - Hubaux, J.-P.
This article provides a technical overview of mobile ad hoc networks and describes their long-term potential. It covers current research, and describes major technical challenges, including networking, real-time services, and software. It shows that by their very nature, mobile ad hoc networks can bring a paradigm shift in the way networks are organized and operated, and can even lead to a fundamental change in the relationships between information technology and societal organization. As an illustration of these concepts, the article also contains an overall description of our long-term research project, called terminodes
Keywords: IP networks; Internet; Cellular networks; Information technology; Long-term research project; Packet radio networks; Real-time services; Research; Self-organized mobile ad hoc networks; Societal organization; Software architecture; Terminodes project